Retirement Timing and Social Stratification. A Comparative Study of Labor Market Exit and Age Norms in Western Europe - Radl, Jonas (De Gruyter, 2013)
The monograph disseminates the very topical issue of retirement and its timing as the key to one of the greatest challenges facing ageing societies. Postponing retirement is now almost universally regarded as indispensable in order to relieve European welfare states from the demography-related financial pressures. This seminal study, derived from a statistical analysis of a large-scale survey data, provides a thorough understanding of the micro- and macro-level determinants of retirement timing in contemporary Western Europe. The book is the first monograph to combine the analysis of the retirement attitudes with the analysis of the retirement behaviour within one research. It tackles the question as to whether early retirement can be explained by "early exit culture", triangulating life course theory with a social stratification approach. The author used a novel and innovative approach to obtain the results. The methodology includes: tobit models of proscriptive age norms; simulations of the impact of class structure on a country's average retirement age; competing risks models of different work-exit modalities; duration selection models of retirement timing.